Small bowel fed response as measured by wireless motility capsule: Comparative analysis in healthy, gastroparetic, and constipated subjects. Issue 5 (18th December 2017) - Surjanhata, B.; Brun, R.; Wilding, G.; Semler, J.; Kuo, B.
Abstract: Background: Small bowel fed response is an increased contractile activity pattern following the ingestion of a meal. Postprandial motility is traditionally evaluated using small bowel manometry. Wireless motility capsule (WMC) is an ingestible wireless capsule that measures pH, temperature, and intraluminal pressure. The primary aim of the study was to assess small bowel fed response captured with the non‐invasive WMC. The secondary aim was to compare the fed response patterns between healthy subjects and patients with motility disorders of gastroparesis and constipation. Methods: All subjects had 250 cc Ensure ® meal 6 hours after WMC ingestion. Frequency of contractions (Ct), area under the curve (AUC), and motility index (MI) were analyzed during 30 minutes of pre‐prandial baseline and 60 minutes postprandially in 20‐minute windows. Key Results: One hundred and eighty‐eight subjects (107 healthy, 23 gastroparetics, 58 constipated) were analyzed. Healthy: Ct, AUC, and MI all increased significantly immediately after meal ingestion ( P  < .01). Motility parameters peak at 20‐40 minutes postmeal. The motor activity decreased at the end of postprandial hour, but was still significantly higher than the fasting baseline ( P  < .01). Gastroparetics : All motility parameters failed to increase significantly compared to the baseline throughout the entire postprandial hour. Constipated: The fed response was similar to healthy subjects. Conclusions and Inferences: The small bowel fed response was readily observed in healthy and chronic constipation subjects with WMC but is blunted in gastroparetics. A blunted small bowel fed response suggests neuropathic changes outside the stomach and may contribute to postprandial symptoms. Abstract : Small bowel fed response is an increased contractile activity pattern following the ingestion of a meal traditionally evaluated using small bowel manometry. Wireless motility capsule non‐invasively detected a blunted fed response in gastroparesis (B) compared to healthy individuals (A). This suggests that neuropathic changes outside the stomach may contribute to postprandial symptoms in gastroparesis.